Rol de enfermería en el asesoramiento nutricional en los pacientes con insuficiencia renal crónica de la Unidad De Hemodiálisis Dial-Ríos octubre 2018 -abril 2019 - Coello Carbo, Marcia Natali (2019)
Visualize the lack of nutritional advice from the nurses in these patients, because as health students and future professionals, the nursing function is to take care of the healthy or sick patient, supporting them in the execution of those activities that contribute to maintaining their quality. life, and be an important axis both in respective functions as well as in nutritional and psychological. It is the one that is aimed at supporting the individual in the conservation of their health and helps to increase that health and is responsible for supporting the recovery of pathological processes. Administration begins whenever an activity is done with more than one person, and in the sanitary environment this is very frequent. By definition, managing is to act consciously on a social system and each of the subsystems that comprise it, in order to achieve certain results. It is a linking activity that allows to take advantage of the capacity and efforts of all the members of an organization, leading them rationally towards the achievement of common objectives. Clear and discernible conceptual structures on clinical roles and associated competencies, including clinical autonomy, could facilitate the decision-making process, as well as lending a degree of logical coherence to the limits of nursing practice and the paths of the profession.